A cross-sectional survey of Blastocystis sp. and Dientamoeba fragilis in non-human primates and their caregivers in Czech zoos - Šejnohová, Anna; Koutenská, Monika; Jirků, Milan; Brožová, Kristýna; Pavlíčková, Zuzana; Kadlecová, Oldřiška; Cinek, Ondřej; Maloney, Jenny G; Santín, Mónica; Petrželková, Klára J; Jirků, Kateřina (One health, 2024)
Intestinal protists in the gut microbiome are increasingly studied, but their basic epidemiology is not well understood. We explored the prevalence, genetic diversity, and potential zoonotic transmission of two protists colonizing the large intestine - Blastocystis sp. and Dientamoeba fragilis - in 37 species of non-human primates (NHPs) and their caregivers in six zoos in the Czech Republic. We analyzed 179 fecal samples (159 from NHPs, 20 from humans) by qPCR. Blastocystis sp. was detected in 54.7% (98/179) of samples, in 24 NHP species and in 57.2% of NHP samples (prevalence ranged between 36 and 80%), and in 35% of human samples (prevalence ranged between 0 and 67%). Using next generation amplicon sequencing, nine Blastocystis subtypes (ST1-ST5, ST7, ST8, and two novel subtypes) were identified. The two new Blastocystis subtypes (named ST47 and ST48) were described using Nanopore sequencing to produce full-length reference sequences of the small subunit ribosomal RNA gene. Some subtypes were shared between NHPs and their caregivers, suggesting potential zoonotic transmission. Mixed subtype colonization was frequently observed, with 52% of sequenced samples containing two or more subtypes. Dientamoeba was found only in NHPs with a prevalence of 6%. This study emphasizes the critical role of molecular diagnostics in epidemiological and transmission studies of these protists and calls for further research to better understand their impact on public health.